Decomposition and forecasting of colorectal cancer burden attributable to high body mass index and high fasting plasma glucose, 1990–2021: A GBD 2021 study - Gao, Ning; Yang, Na; Huang, Juanjuan (Frontiers in Nutrition, 2025)
BackgroundHigh body mass index (HBMI) and high fasting plasma glucose (HFPG), two key metabolic risk factors, are strongly associated with colorectal cancer (CRC). However, systematic quantification of their impact on the global CRC burden—and trends in related health inequalities—remains limited. Using data from the Global Burden of Disease Study 2021, this study assessed the disability-adjusted life years (DALYs) and deaths attributable to HBMI and HFPG in CRC from 1990 to 2021.MethodsDecomposition analysis quantified the contributions of population growth, aging, and epidemiological changes. The concentration index and Lorenz curve assessed health inequality trends, and the Estimated Annual Percentage Change (EAPC) measured burden change rates. Burden trends were projected for 2022–2035 using the Bayesian Age-Period-Cohort (BAPC) model. All indicators were stratified by country, Socio-demographic Index (SDI) tier, gender, and age for comparative analysis.ResultsFrom 1990 to 2021, the burden of CRC attributable to HBMI and HFPG increased, primarily driven by population growth and aging. In high SDI countries, epidemiological changes reduced the burden, while in low- and medium-SDI countries they contributed positively. Although the disease burden remains concentrated in high SDI countries, inequality has declined. Central and Eastern Europe face high DALYs and mortality rates whereas parts of Africa exhibit a lower but rising burden. The burden is primarily concentrated in men over 60. The BAPC model predicts that HBMI- and HFPG-associated DALYs will increase by 47.90 and 41.94%, respectively, while age-standardized DALYs and mortality rates remain relatively stable.ConclusionTargeted strategies focusing on metabolic risk management and early CRC screening—especially in low- and middle-SDI countries—are essential to mitigate the projected burden.